2017
DOI: 10.4314/jmbs.v6i1.2
|View full text |Cite
|
Sign up to set email alerts
|

High efflux pump activity and gene expression at baseline linked to poor tuberculosis treatment outcomes

Abstract: Phenotypic TB drug resistance, also known as drug tolerance, has been previously attributed to slowed bacterial growth in vivo. The increased activity and expression of efflux systems can lower the intracellular concentration of many antibiotics thus reducing their efficacy. We hypothesized that efflux pump activation and expression could be a risk factor for TB drug tolerance in patients initiated on treatment. Analyses of gene expression levels of six select efflux pumps associated with drug tolerance in Myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The expression of Rv1819c in M. smegmatis mc 2 155 was carried out as described earlier (Mazando et al, 2017). Initially, the Rv1819c gene was PCR amplified from the Mtb chromosome and transformed to E. coli DH5α using the pMV261 shuttle vector.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of Rv1819c in M. smegmatis mc 2 155 was carried out as described earlier (Mazando et al, 2017). Initially, the Rv1819c gene was PCR amplified from the Mtb chromosome and transformed to E. coli DH5α using the pMV261 shuttle vector.…”
Section: Methodsmentioning
confidence: 99%
“…It was also reported to get over‐expressed at five folds in Mtb H37Rv (virulent strain) in contrast to H37Ra (avirulent strain) denoting its relationship with Mtb virulence (Målen et al, 2011). Its ciprofloxacin effluxing activity has been previously proven in the heterologous host Escherichia coli BL21‐AI (Mazando et al, 2017). Within the macrophages Mtb survival is based on the ability to inhibit phagosomes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the role played by the ABC superfamily in drug resistance has been the focus of attention in efflux pump-related studies. Rv1819c ( 42 ), Rv0933 ( 38 ), and Rv1217c-Rv1218c ( 43 ) selected from the ABC superfamily in this study have all been reported to be overexpressed in drug-resistance strains or have higher expression level in drug-resistance strains than in sensitive strains. In this study, Rv1819c , Rv0933 , and Rv1217c-Rv1218 were also overexpressed in drug-resistant strains, which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 84%
“…Mycobacterial transformation and expression of recombinant protein : The expression of Rv1218c was carried out as described earlier 24 . Briefly, Rv1218c was overexpressed in the E. coli DH5α strain using the pMV261 vector.…”
Section: Methodsmentioning
confidence: 99%
“…Determination of MIC against recombinant M. smegmatis mc 2 155 (rMSM) and MDR-TB clinical isolates : MICs of the lead molecules (100-1000 µg/ml) in comparison with RMP were determined in triplicates against rMSM and two MDR-TB clinical isolates (RMP MIC >128 and 32 µg/ml), both individually and in combinations. Dilutions were prepared as described previously 24 . In brief, 100 µl of drug solution (RMP and other efflux inhibitors) was added to each first well of the 96 well plate and serially diluted to achieve 2× concentration of the desirable test range.…”
Section: Methodsmentioning
confidence: 99%